Community versus academic hospital community-acquired pneumonia patients: a nested cohort study - Jennifer L.Y. Tsang; Kian Rego; Alexandra Binnie; Terry Lee; Anne Mccarthy; Juthaporn Cowan; Patrick Archambault; Francois Lellouche; Alexis F. Turgeon; Jennifer Yoon; Francois Lamontagne; Allison Mcgeer; et al. (Pneumonia)
Abstract Background Most Canadians receive their care in community hospitals, yet most clinical research is conducted in academic hospitals. This study aims to compare patients with community acquired pneumonia (CAP) treated in academic and community hospitals with respect to their demographics, clinical characteristics, treatments and outcomes. Methods This nested observational cohort substudy of the Community Acquired Pneumonia: Toward InnoVAtive Treatment (CAPTIVATE) trial included 1,329 hospitalized adults with CAP recruited between March 1st, 2018 and September 31st, 2023 from 15 Canadian hospitals. Unadjusted and adjusted analyses for age, sex and co-morbidities using logistic, Cox and censored quantile regressions were conducted. Results Patients in community hospitals were older (mean [SD] 75.0 [15.7] years vs. 68.3 [16.2] years; p < 0.001), were more likely to be female (49.7% vs. 41.0%, p = 0.002), and had more comorbidities (75.9% vs. 64.8%, p < 0.001). More patients in community hospitals received corticosteroids (49.2% vs. 37.4%, p < 0.001). Community hospital patients had a higher likelihood of developing acute respiratory distress syndrome (OR 3.13, 95% CI: 1.87, 5.24, p = < 0.001), and acute cardiac injury (OR 2.53, 95% CI: 1.33, 4.83, p = 0.005). In unadjusted and adjusted analyses, 28-day mortality difference did not meet statistical significance (OR 1.43, 95% CI: 0.98, 20.7, p = 0.062 and OR 1.23, 95% CI: 0.81, 1.87, p = 0.332, respective). Conclusion Patients with CAP in Canadian community and academic hospitals differed with respect to their age, clinical characteristics, treatments and outcomes, emphasizing the importance of including more community hospitals in clinical research studies to ensure the generalizability of results.